Hubungan antara Konsep diri dengan Kepercayaan diri pada Korban Body Shaming - Feri Okta Resa; Christiana Hari Soetjiningsih (Bulletin of Counseling and Psychotherapy, 2022)
As a student, self-confidence is important, both in doing assignments and in carrying out every activity. However, most of the students who are victims of body shaming have low self-confidence. The factor that influences self-confidence is self-concept. Self-concept is a requirement for someone to have self-confidence, where by having a good self-concept one will be able to have a self-confidence. Therefore, this study aims to determine the relationship between self-concept and self-confidence in victims of body shaming. Participants in this study were 34 students of class X in one of the high schools in Salatiga who had experienced body shaming behavior. This study uses a quantitative approach with a correlational design. This study uses a psychological scale as a data collection instrument, namely the self-concept scale and the self-confidence scale. The results of this study indicate that there is a positive and significant correlation (correlation) between self-concept and self-confidence in victims of body shaming with a correlation coefficient value of 0.875 and significance = 0.000 (p < 0.05), which means the higher self-concept, the higher self-confidence. to victims of body shaming and vice versa.